(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Access to safe drinking water remains a persistent public health concern, particularly in educational institutions where students rely on shared water sources for daily consumption. Despite existing water management practices, microbial contamination and water quality issues continue to be reported, indicating the need for sustainable and accessible treatment systems. This study presents the design and development of a solar-powered water purifier prototype and evaluates its effectiveness in improving selected water quality indicators at Mindanao State University–Maigo College of Education, Science and Technology (MSU–MCEST). An experimental-developmental research design was used. The prototype consisted of a solar panel, charge controller, rechargeable battery, power inverter, and a five-stage ultrafiltration system integrated with ultraviolet (UV) sterilization. Water samples were collected from four campus locations—the Senior High School (SHS) Building, Junior High School (JHS) Building, Administration Building, and Peace Park—and were subjected to pre-treatment and post-treatment analyses. Water quality assessment included selected heavy metal indicators using heavy metal test strips and microbiological analysis using bacterial testing kits. Post-treatment results showed reductions in both microbiological contamination and selected chemical indicators. Cadmium (Cd), detected in several untreated samples, was not detected after treatment. Zinc (Zn) remained detectable in one post-treatment sample, indicating limited removal of certain dissolved constituents. All untreated samples tested positive for bacterial contamination, while all treated samples tested negative. These results indicate effective reduction of detectable bacterial contamination, attributed to the ultraviolet (UV) sterilization component under the conditions of the study. Overall, the findings indicate improved microbiological and partial chemical water quality following treatment. However, limitations related to field-based testing methods, sample size, and duration constrain generalization. Further studies using laboratory-based analyses, expanded sampling, and long-term performance evaluation are recommended.